Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Indihome Di Bogor - Muhammad Nasrudin; Saefudin Zuhdi (Jurnal Informatika Kesatuan, 2023)
The need for information and communication technology is also accompanied by an increase in internet users in Indonesia. Many companies are dedicated to technology, information and communication to take advantage of this potential business opportunity. As a result, many companies are offering consumers in the form of digital products and Internet services. One of the companies that will benefit from the development of information and communication technology is PT. Indonesian Telecommunications. The increase in IndiHome Internet users, there are problems with product quality and consumer satisfaction. Customer satisfaction is closely related to service quality. In addition to the problem of service quality to consumers, product quality is also a problem that allows you to provide customer satisfaction. In this study, the research method used by the author is a quantitative research method. In the title of this research, there are three related variables, namely product quality, service quality, and customer satisfaction. Product quality, service quality (X1), (X2), while customer satisfaction is defined as the dependent variable (Y). Variable X1 (Product Quality) has a positive and significant effect on variable Y (Consumer Satisfaction). Variable X2 (Service Quality) has a positive and significant effect on variable Y (Consumer Satisfaction). Product Quality (X1) and Service Quality (X2) variables have a significant effect on purchasing decisions. Keywords : Product Quality, Service Quality, Consumer Satisfaction